Eating Habits Among Medical Students at King Abdulaziz University, Jeddah, Saudi Arabia - Alzahrani,Sami H; Saeedi,Abdulmajeed Abdulaziz; Baamer,Maan Khaleed; Shalabi,Abdullah Faisal; Alzahrani,Abdullah M (International Journal of General Medicine, 2020)
Sami H Alzahrani,1 Abdulmajeed Abdulaziz Saeedi,2 Maan Khaleed Baamer,2 Abdullah Faisal Shalabi,2 Abdullah M Alzahrani3 1Family Medicine Department, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 2Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 3Family Medicine Department, King Saud bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Jeddah, Saudi ArabiaCorrespondence: Sami H AlzahraniFamily Medicine Department, Faculty of Medicine, King Abdulaziz University, P.O. Box 4828, Jeddah 22431, Saudi ArabiaTel +9669500004062Fax +966126408403Email drsamihz@gmail.comBackground: Eating habits are a major concern with regard to the health status of university students. This study aimed to identify patterns of eating habits among undergraduate medical students and to investigate their relationship to sociodemographic, socioeconomic, and psychological factors.Methods: This cross-sectional study included 378 undergraduate medical students aged 19– 26 from the Faculty of Medicine at King Abdulaziz University, Jeddah, Saudi Arabia. Students were in their second through sixth academic year. Data were gathered with a self-administered questionnaire encompassing questions on sociodemographics, eating habits, and psychological factors.Results: Eating habits score was much lower among students who were smokers, lived in rented places, lived alone, had separated parents, and did not exercise regularly. In multivariate analysis, multiple psychological factors, such as living alone and stressed, were found to be associated with eating patterns.Conclusion: A majority of undergraduate medical students had unhealthy eating patterns, and socioeconomic and psychological elements were significantly affecting eating patterns.Keywords: nutrition, survey, dietary habits, psychological factors, sociodemographic factors